2010
DOI: 10.1167/iovs.09-5095
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Angiogenic Potential of Endothelial Cells by Contact with Retinal Pigment Epithelial Cells in a Model Simulating Pathological Conditions

Abstract: Coculture of ECs with RPE under conditions enabling direct EC-RPE contact enhances the proangiogenic potential of ECs under normoxia, to an extent similar to that induced by hypoxia, suggesting that ECs in direct contact with RPE cells might be more prone to pathologic angiogenesis involved in CNV formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Similarly, polarised expression of membrane proteins such as Aquaporin-1, Bestrophin-1, and Na + /K + -ATPase, which play critical roles in exchanging metabolites, may also be observed (Ames et al, 1992;Juuti-Uusitalo et al, 2013;Maminishkis et al, 2006;Stamer et al, 2003). The interaction between RPE cells and the choroidal endothelial cells can also be modelled in culture conditions in order to gain a better understanding of the blood-retinal barrier (Dardik et al, 2010;Hamilton et al, 2007). As well as forming a barrier and interacting with cells of the choroid, RPE cells have an important role in supporting the photoreceptors in the retinoid cycle and phagocytosis of photoreceptor outer segments (POS) and these processes can also be studied in vitro (Ablonczy et al, 2011;Dowling, 1960;Finnemann et al, 1997;Young and Bok, 1969).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similarly, polarised expression of membrane proteins such as Aquaporin-1, Bestrophin-1, and Na + /K + -ATPase, which play critical roles in exchanging metabolites, may also be observed (Ames et al, 1992;Juuti-Uusitalo et al, 2013;Maminishkis et al, 2006;Stamer et al, 2003). The interaction between RPE cells and the choroidal endothelial cells can also be modelled in culture conditions in order to gain a better understanding of the blood-retinal barrier (Dardik et al, 2010;Hamilton et al, 2007). As well as forming a barrier and interacting with cells of the choroid, RPE cells have an important role in supporting the photoreceptors in the retinoid cycle and phagocytosis of photoreceptor outer segments (POS) and these processes can also be studied in vitro (Ablonczy et al, 2011;Dowling, 1960;Finnemann et al, 1997;Young and Bok, 1969).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A better characterization of the homeostatic RPE‐EC relationships is therefore particularly significant. Prior in vitro studies aimed at characterizing such interactions have focused on RPE‐dependent functions in pathological processes, mainly choroidal neovascularization (CNV) and epithelial–mesenchymal transition (EMT), using disease‐mimicking conditions such as hypoxia , direct cell contact , subconfluent or activated RPEs in high serum . While these models provided important insights on the cellular and molecular regulation of EC angiogenic status, the identification of the role of RPE‐EC heterotypic interactions on the formation and maintenance of the outer‐retinal complex requires the use of a more physiological model such as the one described in our study in which human RPE and EC were co‐cultured under quiescent conditions and their interdependent functions directly evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…However, contacting co-culture did not show a difference in response to hypoxia treatment from that of non-contacting co-cultures. Recently, Dardix and coworkers [41] also investigated the effects of co-culture (with retina pigmented epithelial cells - RPE) and hypoxia on endothelial cell expression of VEGF. These researchers reported that contact co-cultures upregulated both VEGF mRNA and protein expression to the same degree as hypoxia alone.…”
Section: Discussionmentioning
confidence: 99%